Edukasi dan Pelatihan Prinsip Ekonomi Syariah dalam Pemanfaatan Minyak Jelantah sebagai Lilin Aromaterapi - Dinanti, Septi Tri; Fitiyani, Yudia Gusti; Julianti, Alda; Yustati, Herlina; Hartini, Kustin (Pakis Journal Institute, 2025)
This education and training program was held at RT 19, Bumi Ayu Village, Selebar District, Bengkulu City, with the aim of providing knowledge and skills to residents, especially housewives, in processing used cooking oil waste into aromatherapy candles that are marketable and environmentally friendly. This training uses an Asset-Based Community Development (ABCD) approach which focuses on utilizing local assets, and combines sharia economic principles such as justice, sustainability, productivity (al-i'mar), and benefit (al-maslahah). The training process includes asset mapping, how to make candles from used cooking oil, and digital marketing strategies via social media. The results of the activity showed an increase in participants' knowledge, technical skills and entrepreneurial motivation. The candle products produced not only help reduce household waste, but also create business opportunities that are halal, innovative and sustainable.